2018
DOI: 10.1186/s12879-018-3250-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characterization of respiratory tract infections caused by Mycoplasma pneumoniae during epidemic and post-epidemic periods in North China, from 2011 to 2016

Abstract: BackgroundMycoplasma pneumoniae (M. pneumoniae) is a commonly causative pathogen for respiratory tract infections (RTIs) in humans. The epidemiological features of M. pneumoniae infections during post-epidemic, including age distribution and the seasonality of the patients, are not well investigated.MethodsWe retrospectively analyzed the clinical data of 7835 consecutive RTIs patients (3852 adults and 3983 children) who visited a teaching hospital, and defined an epidemic (2011–2013) and a post-epidemic period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 38 publications
15
29
0
1
Order By: Relevance
“…In addition, the number of children hospitalized with MP pneumonia in the 2015 epidemic was smaller than that in the 2011 epidemic. These findings were consistent with the results of another study [16]. The reasons for these phenomenon may be associated with exposure to MP in the previous epidemic [7].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the number of children hospitalized with MP pneumonia in the 2015 epidemic was smaller than that in the 2011 epidemic. These findings were consistent with the results of another study [16]. The reasons for these phenomenon may be associated with exposure to MP in the previous epidemic [7].…”
Section: Discussionsupporting
confidence: 92%
“…The number of children hospitalized with MP pneumonia was typically highest between October and November. In the previous studies, the peak incidence of MP pneumonia showed a similar pattern to that observed in the present study, regardless of age [14,16]. However, in the 2011 Korean epidemic, the peak rate of hospitalization due to MP pneumonia in children occurred in September, whereas the peak rate in the 2015 epidemic occurred in November.…”
Section: Discussionsupporting
confidence: 88%
“…M. pneumoniae was observed in three groups, and the positive rates of the children group and the old adult group are higher than that of group 16 -49 years, in China, M. pneumoniae is reported as one of the most common pathogen of patients with CAP and it is an unexpected result in our study [25,28].…”
Section: Discussionmentioning
confidence: 49%
“…Qu und Kollegen haben 2011 bis 2016 die Häu gkeit und saisonale Verteilung von respiratorischen Infektionen bei Kindern und Jugendlichen untersucht [14]. Die Diagnose wurde aus respiratorischen Spezimen mit PCR-Nachweis gestellt.…”
Section: Mykoplasmen Und Chlamydienunclassified